The Effect of PjBL on Critical Thinking Skills of High School Students in Physics Learning on Topic of Static Fluid - Maemum, Putri Julia; 'Ardhuha, Jannatin; Sutrio, Sutrio; Wahyudi, Wahyudi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
In the 21st century, students are required to possess a variety of skills to face the challenges of the times, one of which is critical thinking. Educational activities, including physics instruction, serve as an important medium for fostering these skills. However, physics is often perceived as a challenging subject, primarily due to the dominance of teacher-centered learning models. This highlights the need for student-centered approaches that actively engage learners in the educational process. One such approach is the Project-Based Learning (PjBL) model. This study aims to examine the effect of the PjBL model on students' critical thinking skills in physics learning, specifically on the topic of static fluids. The hypotheses tested in this study are: H₀ (there is no significant effect of the PjBL model on students’ critical thinking skills) and Hₐ (the PjBL model has a significant effect on students’ critical thinking skills). The research employs a quasi-experimental design with a control group. The population consists of Grade XI students at SMA IT Abu Hurairah Putri, Mataram City. A saturated sampling technique was used, with class XI MIPA 1 assigned as the experimental group and XI MIPA 2 as the control group. The research instrument was a critical thinking test comprising four questions, all of which were previously validated and proven reliable. Data analysis was conducted using the Mann-Whitney U test at a 5% significance level. The results indicate a p-value of 0.001, which is less than the threshold of 0.05. Thus, the null hypothesis (H₀) is rejected, leading to the conclusion that the PjBL model has a significant effect on students' critical thinking skills.